Reliability and validity estimation of Urdu version of Children Emotion Management Scales (CEMS) in Pakistan - Baig, Khawer Bilal; Sadia, Haleema; Rauf, Umara; Abbas, Qasir; Ramzan, Zoobia; Tabassum, Urooj; Aljhani, Sumayah (Frontiers in Psychiatry, 2024)
Introduction The present study aimed to translate and validate Children's Emotion Management Scales into Urdu, the national language of Pakistan. Method The current study comprised three different phases, i.e., phase I: Cross-language validation over a sample of (N = 169) school children, estimated at a 1-week interval. Results The results indicate a significant correlation (r = 0.846–0.891) at p < 0.01. In phase II, the internal consistency reliability (r = 0.808–0.904) and split-half reliability (r = 0.737–0.898) of the scale were assessed (N = 683) at p < 0.01. Furthermore, significant results for test-retest reliability analysis (N = 168) were obtained (r = 0.736–0.917 at p < 0.01), following the confirmatory factor analysis (CFA) (N = 1,083). Exploratory factor analysis (EFA) was conducted on the same sample chosen for CFA. EFA resulted in the retention of original inhibition (INH), dysregulated expression (DYS), and emotional coping (EMO) factors. CFA findings suggest a good model fit. In phase III, convergent validity and divergent validity were checked (N = 385, 255, and 213). Convergent validity of INH and DYS subscales and divergent validity of EMO subscales were established, with SBI (r = 0.217–0.609; 0.210–0.445; −0.026 to −0.553), SHS (r = 0.417–0.441; 0.480–0.546; −0.338 to −0.582), and suppression subscale of ERQ (r = 0.430–0.480; 0.468–0.522; −0.245 to −0.369) at p < 0.01. For divergent validity of INH and DYS subscales and convergent validity of EMO subscales, their scores were correlated with the SPS (r = −0.204 to −0.350; −0.318 to −0.459; 0.191–0.531), RSE Scale (r = −0.226 to −0.351; −0.279 to −0.352; 0.255–0.507), DTS (−0.290 to −0.617; −0.369 to −0.456; 0.246–0.680), and reappraisal subscale of ERQ (r = −0.456 to −0.541; −0.329 to −0.544; 0.446–0.601) at p < 0.01. Discussion It is concluded that the scale is reliable and valid with sound psychometric properties.